Large-amplitude oscillatory shear behavior of xanthan gum/locust bean gum mixture: Effect of preparation methods on synergistic interaction - Ozmen, Duygu; Toker, Omer Said (WILEY, 2022)
Large-amplitude oscillatory shear (LAOS) is a technique used for determining the rheological properties of food materials to simulate processes from production to consumption in food chains that can cause high deformations in the product. Hydrocolloids are frequently used alone or in combination with various hydrocolloids to control product's texture and rheology. In this study, LAOS behavior of xanthan gum (XSG) and locust bean gum (LBG) mixtures at different concentrations (0.1%, 0.3%, and 0.5%) was investigated and 3ITT was employed for supporting the LAOS findings. Also, different preparation methods (mixing before (BH) and after hydration (AH) and with powder forms (P)) were studied. LBG solution had viscous properties at all concentrations, while XSG solution showed elastic behavior at 0.3% and 0.5% concentrations. Mixture solutions' elasticity was much more dominant than viscous behaviors according to XSG and LBG solutions alone due to synergistic interaction. According to Lissajous-Bowditch curves, AH has lower elasticity values than BH and P solutions. At higher strain values, BH and P solutions had more resistance. The recovery ability of the samples acquired from 3ITT increased with increasing gum concentration (e.g., for BH solutions from 0.1% to 0.5% concentrations recovery values increased from 91.19% to 97.82% at 10% strain value) and decreased with strain values (e.g. for BH solutions at 0.1% concentrations recovery values decreased from 91.19% to 25.77% from 10% strain value to 500% strain value), in accordance with the S and T values and Lissajous-Bowditch curves where the samples having viscouscharacter showed low recovery %.
Keywords: 3ITT; hydrocolloids; LAOS; locust bean gum; xanthan gum; LAOS BEHAVIOR; GELATIN; Engineering; Food Science & Technology